A relação entre constituição da identidade de gênero e brincadeiras infantis no ambiente escolar - MARTINS, Flaviane Cordeiro (2025)
This research looks at the relationship between the constution of gender identity and children's games in the school environment, more specifically in the playroom of a nursery school. The main objectives of the research is to analyze how children's games produce or reproduce gender identities in the educational context, as well as to identify the socially and culturally preestablished values and behaviors that are “normalized” in children's games, according to gender, and to verify the impact of the division of games and toys by gender in the school space on children. For the theoretical basis of this discussion, we considered contributions from renowned authors such as Louro (1997,1999), Silva (2000) and Hall (2006), who have research in the areas of Cultural and Feminist Studies. In addition, researchers such as Barros (2009), Brougère (2010) and Felipe (2003) also provided a basis on the importance of play and its influence on children's upbringing based on cultural and social aspects. This study adopted a post-critical approach to research and analysis, using ethnographic approaches to understand the general aspects and, above all, the subjectivity of the subjects involved. Participant observation was used to capture the movements and daily life of the research, while the conversation method allowed participants to express themselves freely and share their experiences. In addition, the use of images was employed to deepen understanding of the more intrinsic aspects of the research. The results highlight problematic issues that go beyond the playroom, showing that the construction of gender identity is also influenced by factors outside the school, and that children carry with them cultural values that are very well established in their social backgrounds, so it is important to emphasize that the division of games and toys by gender experienced in everyday school life can contribute to the perpetuation of stereotypes, affecting children's development. However, there is hope for change through the transformation of pedagogical practices, aiming to build a policy that values equity in children's play. In short, this work highlights the need to rethink educational practices, promoting an inclusive school environment in which children have the freedom to explore a variety of games, regardless of their gender. The research highlights the importance of creating spaces in which children can express themselves freely, challenge gender stereotypes and develop a broader understanding of human diversity.